A Narrative Review on the Pandemic Zoonotic RNA Virus Infections Occurred During the Last 25 Years - Gobena Ameni; Aboma Zewude; Begna Tulu; Milky Derara; Berecha Bayissa; Temesgen Mohammed; Berhanu Adenew Degefa; Mohamed Elfatih Hamad; Markos Tibbo; Robert Barigye (Journal of Epidemiology and Global Health)
Abstract Background Pandemic zoonotic RNA virus infections have continued to threaten humans and animals worldwide. The objective of this review was to highlight the epidemiology and socioeconomic impacts of pandemic zoonotic RNA virus infections that occurred between 1997 and 2021. Methods Literature search was done from Web of Science, PubMed, Google Scholar and Scopus databases, cumulative case fatalities of individual viral infection calculated, and geographic coverage of the pandemics were shown by maps. Results Seven major pandemic zoonotic RNA virus infections occurred from 1997 to 2021 and were presented in three groups: The first group consists of highly pathogenic avian influenza (HPAI-H5N1) and swine-origin influenza (H1N1) viruses with cumulative fatality rates of 53.5% and 0.5% in humans, respectively. Moreover, HPAI-H5N1 infection caused 90–100% death in poultry and economic losses of >$10 billion worldwide. Similarly, H1N1 caused a serious infection in swine and economic losses of 0.5-1.5% of the Gross Domestic Product (GDP) of the affected countries. The second group consists of severe acute respiratory syndrome-associated coronavirus infection (SARS-CoV), Middle East Respiratory Syndrome (MERS-CoV) and Coronavirus disease 2019 (COVID-19) with case fatalities of 9.6%, 34.3% and 2.0%, respectively in humans; but this group only caused mild infections in animals. The third group consists of Ebola and Zika virus infections with case fatalities of 39.5% and 0.02%, respectively in humans but causing only mild infections in animals. Conclusion Similar infections are expected in the near future, and hence strict implementation of conventional biosecurity-based measures and development of efficacious vaccines would help minimize the impacts of the next pandemic infection.